Fungsi Lembaga Pemasyarakatan dalam Melaksanakan Pembinaan terhadap Warga Binaan Pemasyarakatan (WBP) (di Lembaga Pemasyarakatan Perempuan Kelas II A Denpasar) - I Wayan Kevin Mahatya Pratama; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Correctional in its system is useful for preparing convicted people in prisons to integrate normally and be accepted in society again. Merging normally again means restoring the relationship between the convicted or often referred to as Correctional Assistance and the community. The Penitentiary is a place for the Community Assisted to serve their sentence. This study aims to determine the function of prisons in carrying out coaching for Correctional Assistance and to analyze the form and benefits of the guidance program for Correctional Assistance held at Class II-A Denpasar Women's Penitentiary. This research uses normative legal research methods. The data obtained through direct observation in the field. The results showed that in the Guidance Program of the Correctional Institution, especially the location of this research, was held, namely the Class IIA Denpasar Women's Penitentiary, which has collaborated with government agencies, private foundations, and community organizations engaged in the field of women in providing guidance as well as promoting the work of prisoners or residents. Correctional Assistance. In addition, the Class IIA Denpasar Women's Penitentiary held and participated in several exhibitions of the work of the Community Assisted Citizens. This activity aims to introduce the work of the Community Assisted Citizens to the community and make it clear that the Correctional Institution guides or fosters Prisoners to be able to work and be able to contribute to society when they finish serving their sentence.